Use of Social Media by Employees During Work Hours - Case Study: Employees of the Saudi Telecom Company STC - Shaya, Mohammed Faris (Journal of Economic, Administrative and Legal Sciences, 2019)
The current study aimed at investigating the reasons for using social media by employees of the Saudi Telecom Company STC during working hours, revealing the most prominent negative effects of using social media by employees during working hours, from their own perspectives, and revealing the existence of statistically significant differences among employees’ responses, based on the variables (Gender-Educational Qualification- Years of Experience). The study sample included (15) employees of the Saudi Telecom Company (STC). To achieve the study objectives, the researcher adopted the analytical descriptive approach as the research methodology and used the questionnaire as the research instrument for data collection. The researcher reached several results, most notably is that “Reasons for using social media by employees during working hours” scored (high) from the perspectives of study respondents and “Negative effects of using social media by employees during working hours” scored (very high) from the perspectives of study respondents.
Keywords: Social Media; Work Hours; Employees; Work Performance; STC